EFFECT OF ORGANIZATIONAL COMMITMENT AND TASK CHARACTERISTICS ON EMPLOYEE PERFORMANCE SHIPPING COMPANY IN SURABAYA CITY - Setiono, Beni Agus; Sapit Hidayat (Archives of Business Research, 2021)
The purpose of this study was to prove and analyze the effect of organizational commitment and task characteristics on the performance of shipping company employees in the city of Surabaya. This research is an explanatory research with a quantitative approach because it explains the influence between variables through hypothesis testing. This research was conducted in the city of Surabaya with a focus on shipping companies. The population in this study were the managers of shipping companies in the city of Surabaya from 101 shipping companies. The sampling method used proportional random sampling. The number of samples used in this study was 101 x 20% = 20 respondents. This study found that organizational commitment had no effect on employee performance at shipping companies in Surabaya. Task characteristics have a significant effect on employee performance at shipping companies in Surabaya. Together, organizational commitment and task characteristics have a significant effect on employee performance at shipping companies in Surabaya.